Analyze of general rainfall trend in Al Dayra’a basin in Hail region (Saudi Arabia) during the period 1976-2017 - Alkhuraiji, Wafaa; Alhasher, Fahdah; Aldosari, Ali; Al Farhan, Mohammed (Dirasat: Human and Social Sciences, 2021)
Rain is one of the most important climatic elements in the arid and semi-arid regions because of its extreme importance in human life and its impact on its daily activities in all fields. With increasing attention to climate change, the climate research has gradually tended to analyze the rainfall trends. So, this study deals to analyze the rainfall general trend in the Wadi Al Dayra’a basin located in Hail region. It is based on the maximum daily and annual rainfall data for a continuous period of 42 years from January 1976 to December 2017 in seven stations namely Al Hait, Semayra, Baqaa, Hail, Al Ghazala and Uqlat Bin Jibreen and Jabbah. This study used several statistical methods to examine the rain data quality, Normality test using Shapiro-Wilk test, Homogeneity of variances using Levene test and ANOVA test. In order to analyze the rainfall general trend, this study was based on the application of three other statistical methods, named the ratio of Semi Means, Binomial test and Semi Means. The “t” student test was applied to determine a significance of the Semi means method results. The results of the Semi Means and Binomial tests confirmed the decreasing of of annual and daily maximum rainfall trends in all the studied stations. While the results of "t" student test confirmed the decreasing maximum daily rainfall trends in Semayra, Al Hait, Hail and Al Ghazala stations and the decreasing annual rainfall trends in Semayra, Al Hait, Uqlat Bin Jabreen and Al Ghazala.